Counter-ion and solvent effects on the acidity of calix[4]arene and para-tert-butylcalix[6]arene - Miñambres, Guadalupe Gloria (2015)
Spectrophotometric titrations of calix[4]arene and p-tert-butylcalix[6]arene with LiOH, NaOH, KOH, tetramethylmmonium and tetrabutylammonium hydroxides as bases were carried in ethanol 95 % and acetonitrile. The dependence of pKa of the first deprotonation of calix[4]- arene with the nature of the cation was only modest in ethanol 95 %, spanning from 8.53 pKa unit for NaOH until 9.00 for LiOH, whereas in acetonitrile the proton transfer is quantitative. The first deprotonation of p-t-butylcalix[ 6]arene in both solvents is quantitative and the extension of the second deprotonation is very dependent of the nature of the cation in ethanol and acetonitrile. Tetramethylammonium hydroxide was the strongest base for both solvents, and both deprotonations proceed quantitatively and concomitantly in ethanol, followed by potassium hydroxide, and the weakest base was tetrabutylammonium hydroxide. This behavior indicates that the ability to form N+-C-H-π and K+-π interactions plays an important role to stabilize the mono and dianion calixarene. Lithium and sodium exhibit non-usual acid-base behavior in acetonitrile, attributed to aggregation of the species.